2004
DOI: 10.1189/jlb.1003462
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Jagged-1 is able to inhibit the function of its multivalent form to induce hematopoietic stem cell self-renewal in a surrogate in vitro assay

Abstract: Stem cells reside in customized microenvironments (niches) that contribute to their unique ability to divide asymmetrically to give rise to self and to a daughter cell with distinct properties. Notch receptors and their ligands are highly conserved and have been shown to regulate cell-fate decisions in multiple developmental systems through local cell interactions. To assess whether Notch signaling may regulate hematopoiesis to maintain cells in an immature state, we examined the functional role of the recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 31 publications
1
58
0
Order By: Relevance
“…The biological roles of soluble Notch ligands are insufficiently understood, although we know that naturally occurring soluble forms of Notch ligands arise due to proteolytic cleavage (Qi et al, 1999), including the cleavage stimulated by their interaction with Notch receptors (Ikeuchi and Sisodia, 2003;LaVoie and Selkoe, 2003) or differential mRNA processing (Zimrin et al, 1996;Li et al, 1997;Aho, 2004). Several reports indicate that soluble forms of Jagged1 may play crucial roles in hematopoietic and nerve stem cell self-renewal, cell proliferation, angiogenesis, and vascular repair (Masuya et al, 2002;Vas et al, 2004;Nikopoulos et al, 2007;Scehnet et al, 2007). Our in vitro studies demonstrated that fibroblastoid cells expressing sJ1 117-kDa form chord-like structures, similar to those formed by endothelial cells during angiogenesis (Wang et al, 2000;Small et al, 2001;Trifonova et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The biological roles of soluble Notch ligands are insufficiently understood, although we know that naturally occurring soluble forms of Notch ligands arise due to proteolytic cleavage (Qi et al, 1999), including the cleavage stimulated by their interaction with Notch receptors (Ikeuchi and Sisodia, 2003;LaVoie and Selkoe, 2003) or differential mRNA processing (Zimrin et al, 1996;Li et al, 1997;Aho, 2004). Several reports indicate that soluble forms of Jagged1 may play crucial roles in hematopoietic and nerve stem cell self-renewal, cell proliferation, angiogenesis, and vascular repair (Masuya et al, 2002;Vas et al, 2004;Nikopoulos et al, 2007;Scehnet et al, 2007). Our in vitro studies demonstrated that fibroblastoid cells expressing sJ1 117-kDa form chord-like structures, similar to those formed by endothelial cells during angiogenesis (Wang et al, 2000;Small et al, 2001;Trifonova et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show that Notch facilitates bone marrow stem cell expansion and plays a role in the stem cell niche in vivo (11). In vitro activation of Notch in hematopoietic stem cells leads to increased proliferation and survival (13,49). Notch signaling facilitates T-cell development and plays a role in biphenotypic fate decisions (24).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble, non-membrane bound ligands have been shown to retain signaling activity in some, but not all, cultured cell assays (Hicks et al, 2002;Li et al, 1998;Ohishi et al, 2002;Shimizu et al, 2000;Shimizu et al, 2002;Vas et al, 2004;Wang et al, 1998). The antibody-induced oligomerization of soluble ligands, which were produced as fusions with human IgG Fc, has been reported to increase the signaling activity of these ligands, suggesting that ligand clustering promotes signaling (Hicks et al, 2002;Shimizu et al, 2002).…”
Section: Is Ligand Endocytosis Always Required For N Activation?mentioning
confidence: 99%